(untitled) (Archaeologia Adriatica, 2009)
In his great work Procopius of Caesarea provided some facts about the eventful life of Ildigis, successor to the Langobard throne, who had never actually become king. The Byzantine author mentions also the tribe of Slavs which is very important for their history in the 6th century. Long-lasting discussions among historians have not led to the creation of one standpoint concerning the localization of settlements of the Slavic allies of Ildigis. The growing amount of archeological sources relating to this problem enables archeologists to participate in this discussion also. The article discusses possible interpretations of Procopius’ words and different ideas about precise localization of Slavic settlements mentioned by him. Those theories are confronted with available archeological data, especially because modern methods allow precise dating of archeological finds and the increasing volume of archaeological data from Croatia, Slovenia, Romania and other countries, enables the presentation of a new approach to the problem of earliest Slavic settlements.